2011
DOI: 10.1074/jbc.m111.256164
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Adhesion Molecule (EpCAM) Complex Proteins Promote Transcription Factor-mediated Pluripotency Reprogramming

Abstract: Background: EpCAM is highly expressed in ESCs. However, the role of EpCAM complex proteins in pluripotency reprogramming is still unknown. Results: Overexpression of EpCAM complex proteins significantly repressed the expression of p53 and enhanced reprogramming efficiency in MEFs. Conclusion: EpCAM signaling enhance reprogramming through suppression of the p53-p21 pathway. Significance: EpCAM signaling enhance reprogramming through suppression of the p53-p21 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 52 publications
6
84
0
Order By: Relevance
“…In addition, several reprogramming genes, such as NANOG, SOX2, NOTCH, and LIF, have been found to intensely promote tumorsphere formation and tumor initiation (9,24,25). Alternatively, up-regulation of EpCAM has been shown both to increase the reprogramming process of induced pluripotent stem cells by suppressing p53 and p21 expression and to maintain undifferentiated status of ESCs through the controlling of the pluripotent gene expression (13,14,26). However, there has been no direct evidence linking the regulation of EpCAM in these reprogramming genes in TICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several reprogramming genes, such as NANOG, SOX2, NOTCH, and LIF, have been found to intensely promote tumorsphere formation and tumor initiation (9,24,25). Alternatively, up-regulation of EpCAM has been shown both to increase the reprogramming process of induced pluripotent stem cells by suppressing p53 and p21 expression and to maintain undifferentiated status of ESCs through the controlling of the pluripotent gene expression (13,14,26). However, there has been no direct evidence linking the regulation of EpCAM in these reprogramming genes in TICs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the expression of EpCAM is involved in the reprogramming process of induced pluripotent stem cells (14). Therefore, it is necessary to unveil the mechanism and functional roles of EpCAM and EpICD in TICs.…”
mentioning
confidence: 99%
“…17, 18, 20, 21, 27, 58, 83, 93-98). Interestingly, recent studies showed that some of these liver CSC markers are also functionally involved in the maintenance of (99,100), and CD133 expression is required for the maintenance of CD133 + liver CSCs through neurotensin/ IL-8/CXCL1 signaling activation (101). In addition, a CD44 variant regulates the redox status by stabilizing xCT and protecting CSCs from oxidative stress (102), while CD13 reduces cell damage induced by oxidative stress after exposure to genotoxic reagents (19).…”
Section: Shared Features Of Liver Development and Liver Cancer Develomentioning
confidence: 99%
“…Interestingly, Zeb1 (a known transcription factor inducing EMT) represses both E-cadherin and EpCAM by binding to the EpCAM promoter [133], yet the expression of E-cadherin and EpCAM is related to a stem cell-like phenotype [134,135]; in basal-like breast cancer, EpCAM and P-cadherin both appear to be associated with the CSC phenotype [108]. As described for the hallmarks of cancer [33], the timing and ordering of these events appears to differ between normal and tumourous tissues, between different tissue and tumour types, and most likely within the same tumour.…”
Section: Cadherins and Epcammentioning
confidence: 99%